2020
DOI: 10.1111/1471-0528.16604
|View full text |Cite
|
Sign up to set email alerts
|

Cervical dilatation and preparation prior to outpatient hysteroscopy: a systematic review and meta‐analysis

Abstract: Background There are uncertainties about the benefit of routine cervical preparation and/or cervical dilatation before outpatient hysteroscopy. Objective To determine if cervical preparation and/or routine mechanical dilatation reduces pain during outpatient hysteroscopy. Search strategy MEDLINE, EMBASE, CINAHL and CENTRAL were searched on 19 October 2020, using keywords ‘hysteroscopy’, ‘cervical preparation’, ‘cervical ripening’, ‘cervical dilatation’, ‘outpatient’, ‘office’ and/or ‘ambulatory’ and associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Preoperative priming of the cervix eases entry into the cavum and allows further dilatation, which can shorten the operation time. However, significantly more side effects such as bleeding, abdominal pain, and gastrointestinal symptoms occur under this [ 24 ]. Oral and vaginal administration of misoprostol appear equivalent, but side effects such as diarrhea are less common with vaginal administration [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative priming of the cervix eases entry into the cavum and allows further dilatation, which can shorten the operation time. However, significantly more side effects such as bleeding, abdominal pain, and gastrointestinal symptoms occur under this [ 24 ]. Oral and vaginal administration of misoprostol appear equivalent, but side effects such as diarrhea are less common with vaginal administration [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical priming facilitated hysteroscopy by dilating the cervix, allowing for easier entry and reducing procedural time. Administration of a cervical preparation, however, increased the risk of adverse effects, namely genital tract bleeding, abdominal pain/cramping and gastrointestinal disturbance [18].…”
Section: Preparation Of the Cervix With Vaginal Misoprostolmentioning
confidence: 99%
“…Due to similarity in the mechanism of action, we believe that vaginal dinoprostone exhibits similar time-dependent efficacy as demonstrated in misoprostol; however, this was not previously investigated in randomized controlled trials (RCTs). Additionally, a recent systematic review by De Silva et al [30] concluded that uncertainties still remain regarding the ideal dose, timing, and route of PG administration before OH. They advised further research to identify the optimal cervical preparation regimen with regards to the timing of administration.…”
Section: Introductionmentioning
confidence: 99%